АМУДАРЁ БЎЛИМИДА СУД – ҲУҚУҚ ТИЗИМИНИНГ ШАКЛЛАНИШИ - Абдуллаев, А.; Ктайбеков, А. (SCIENCE and SOCIETY, 2021)
The article deals with earliest stage of formation of judicial law system in Amudarya region of the XIX-th century. There was organized an expedition on studying the activity of the system. On the whole there were studied the works of Regional and People’s Courts, State Prosecutor’s Office and Barristers Colleges, notary, officers of court and kaziy (local judge) courts. There is given attention to execution of judicial sentences and verdicts. There were made conclusions and analysed the activity and territorial locations of judicial bodies of the region.